2018
DOI: 10.3389/fpsyt.2018.00461
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Cognitive Remediation for Psychiatric Disorders: A Review

Abstract: Cognition is an important factor that affects daily functioning and quality of life. Impairment in cognitive function is a common symptom present in various psychological disorders, which hinders patients from functioning normally. Given that cognitive impairment has devastating effects, enhancing this in patients should lead to improvements in compromised quality of life and functioning, including vocational functioning. Over the past 50 years, several attempts have been made to improve impaired cognition, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 163 publications
(217 reference statements)
5
53
0
Order By: Relevance
“…Methodology varied significantly among the included reports and quality ratings were moderate on average. Cognitive enhancement interventions showed positive findings for cognitive and functional outcomes, but these were not robust and can only be considered preliminary, which is in line with recent relevant reviews …”
Section: Discussionsupporting
confidence: 67%
“…Methodology varied significantly among the included reports and quality ratings were moderate on average. Cognitive enhancement interventions showed positive findings for cognitive and functional outcomes, but these were not robust and can only be considered preliminary, which is in line with recent relevant reviews …”
Section: Discussionsupporting
confidence: 67%
“…Although this research is still in its infancy [26], increasing evidence suggests that patients with addictive disorders may benefit from cognitive remediation therapy of working memory (or other cognitive processes). Nevertheless, controversies regarding its efficacy have emerged.…”
Section: Resultsmentioning
confidence: 99%
“…For example, findings may help provide direction for prescription of cognitive remediation interventions designed to target attention, working memory, and other cognitive deficits in ADHD. Currently, there is mixed support regarding whether not neurocognitive remediation training improves working memory and sustained attention in non-Hispanic children with ADHD (Johnstone et al, 2012;Kim et al, 2018;Orban et al, 2014;Rapport et al, 2013). Among Puerto Rican children, a recent study by Medina (2018) found preliminary evidence that cognitive training improves reading and other cognitive processes (e.g., attention, successive processing, and simultaneous processing).…”
Section: Discussionmentioning
confidence: 99%